Has the time come for de-escalation in the management of oropharyngeal carcinoma? - Durkova, Jana; Boldis, Martin; Kovacova, Slavomira (Biomedical papers, 2019)
Over the course of the last two decades, there has been a decrease in the incidence of head and neck cancers thanks to a decreasing prevalence of smoking. However, a new risk factor has been coming to the fore: human papillomavirus infection (HPV). HPV-positive oropharyngeal squamous cell carcinoma (HPV+OPC) is more sensitive to chemotherapy and radiotherapy, which translates to a much better prognosis with conventional treatment protocols than tumours that are HPV-negative. Traditional therapeutic interventions are associated with substantial morbidity and have a great impact on patient quality of life. The main focus is on identifying an ideal group of HPV-positive patients who could receive de-intensification treatment regimens aimed at avoiding the late toxicity of treatment. Various strategies are considered, such as reduction in radiotherapy dose following induction chemotherapy, radiotherapy alone, minimally invasive surgical techniques, and substituting platinum-based chemotherapy. The first generation of de-escalation randomised phase III trials have now been published. The following review summarizes the current knowledge and treatment of oropharyngeal carcinoma.
Keywords: oropharyngeal carcinoma; human papillomavirus (HPV); treatment de-escalation/de-intensification; prognostic and predictive markers